Pengaruh Variabel Publik dan Non Publik Terhadap Pertumbuhan Ekonomi di Indonesia - Kristoper Haryanto; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to analyze the effect of public investment, private investment, labor, public economic institutions on economic growth in 33 provinces of Indonesia. The data used in this study is panel data from 2015 to 2019 taken from the Indonesian Central Statistics Agency (BPS), the Investment Coordinating Board (BKPM), and the Ministry of Finance of the Republic of Indonesia. This study uses panel data regression analysis with public investment, private investment, labor, and public economic institutions as independent variables and economic growth as the dependent variable. The results of the study are that public investment, private investment, and labor have a positive and significant impact on economic growth and public economic institutions have a positive and insignificant effect on economic growth in 33 provinces of Indonesia.